The impact of information on clinical decision making by General Medical Practitioners - Frances Wood; Pamela Wright (Information Research: An International Electronic Journal)
Summarises some of the principal findings of a recent study investigation of information usage by general medical practitioners (GPs). The work was based on previous studies of the value and impact of information, these studies being undertaken in the corporate sector in Canada, the USA and the UK. The study used a critical incident technique similar to that employed in the Canadian and USA studies. Twenty seven in-depth interviews were conducted with general practitioners (GPs) in the Trent Health Region (only one from each practice). The sample, selected from two health districts, included large, medium and small practices, fund-holding and non-fund-holding practices, and training and non-training practices, with some representation of those located in deprived and non-deprived (socio-economic) areas.